The Influence of Islamic Boarding School Culture in Indonesian Tafsir: A Study of Tafsir Tamsyiyyatul Al-Muslimin by KH. Ahmad Sanusi - Masruchin Masruchin; Anjela Kharomah; Muhammad Pandu; Riduan Alhuda; Antara Sabastian (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
This study seeks to examine how pesantren culture influences patterns of interpretation in one of the works of Nusantara exegesis, namely the Tamsyiyyat al-Muslimin exegesis compiled by KH. Ahmad Sanusi. Using a qualitative-descriptive approach, the study explores the relationship between pesantren experiences, turats traditions, surrounding scientific relations, and the moral ethos that shaped Sanusi's understanding and delivery of the messages of the Qur'an. The results of the study show that the pesantren tradition is not only a biographical background, but also functions as an epistemological foundation that guides the pattern of interpretation of verses, the selection of classical references, the Shafi'i fiqh style, and the way of contextualizing the teachings of the Qur'an with the social conditions of society during the colonial period. This interpretation uses the ijmali method, communicative language, and social criticism rooted in the role of the kiai as an educator of society. This research shows that Tamsyiyyat al-Muslimin is a unique representation of pesantren interpretation that emphasizes the close relationship between scholarly tradition, pedagogy, and the construction of interpretive thought in the archipelago.